2015
DOI: 10.1371/journal.pone.0131050
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Multiple Brachyspira hyodysenteriae Genomes Confirms That the Species Is Relatively Conserved but Has Potentially Important Strain Variation

Abstract: The intestinal spirochete Brachyspira hyodysenteriae is an important pathogen in swine, causing mucohemorrhagic colitis in a disease known as swine dysentery. Based on the detection of significant linkage disequilibrium in multilocus sequence data, the species is considered to be clonal. An analysis of the genome sequence of Western Australian B. hyodysenteriae strain WA1 has been published, and in the current study 19 further strains from countries around the world were sequenced with Illumina technology. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 33 publications
6
34
0
Order By: Relevance
“…The sequences for hlyA were identical to the whole genome sequences of WA1 and the 18 additional strains [ 47 ], except strain 3bIII and 4cI, which differed with regard to two nucleotides. However, these nucleotide differences were synonymous and did not translate into a different amino acid sequence.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The sequences for hlyA were identical to the whole genome sequences of WA1 and the 18 additional strains [ 47 ], except strain 3bIII and 4cI, which differed with regard to two nucleotides. However, these nucleotide differences were synonymous and did not translate into a different amino acid sequence.…”
Section: Resultsmentioning
confidence: 88%
“…Furthermore, all sequences were compared to the whole genome sequences of 18 additional B. hyodysenteriae strains, including type strain B78 and reference strains B204 and FM88.90. These whole genome sequences were recently described by Black et al [ 47 ].…”
Section: Methodsmentioning
confidence: 99%
“…They included the sequences of the 4 B. pilosicoli strains 95/1000, WesB, B2904 and P43/ 6/78 T (accession numbers NC_014330, NC_018604, NC_018607 and NC_019908, respectively), 20 Brachyspira hyodysenteriae strains (accession numbers NC_012225 for the chromosome and NC_012226 for the plasmid of WA1, and NZ_JXNA00000000 through NZ_JXNS00000000 for the other 19 strains: Black et al, 2015), 5 'Brachyspira hampsonii' strains (accession numbers NZ_ALNZ00000000 and NZ_AOMM00000000, and 3 unpublished), 2 Brachyspira intermedia strains (NC_017243 and 1 unpublished), 1 Brachyspira innocens strain (NZ_ARQI00000000), 1 Brachyspira murdochii strain (NC_014150), 1 Brachyspira alvinipulli strain (NZ_JADF00000000), 1 Brachyspira aalborgi strain (unpublished) and 1 'Brachyspira suanatina' strain (NZ_CVLB00000000).…”
Section: Analysis Of Whole Genome Sequencesmentioning
confidence: 99%
“…A major contribution of the study by Thorell lack the 36-kb plasmid thought to be important in pathogenesis (20). The B. aalborgi genomes have the characteristic low GϩC content of Brachyspira (28.1 to 28.3%) and are otherwise similar to genomes of the 8 other Brachyspira species for which sequences are available (20,21).…”
mentioning
confidence: 99%
“…Intraspecies comparisons of the B. aalborgi genomes revealed a heterogeneity greater than expected, although the organisms were clearly separated from other species. Black et al (20) found that the genomes of B. hyodysenteriae strains had undergone significant rearrangements, and the heterogeneity in B. aalborgi may also be related in part to rearrangements. Availability of the B. aalborgi sequences will extend the comparative genomics possibilities within the Brachyspira genus, perhaps helping to reveal key differences important in host interactions, such as pathogenesis or host range (21).…”
mentioning
confidence: 99%